2003
DOI: 10.1556/abiol.54.2003.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Catalase activity in arctic microfungi grown at different temperatures

Abstract: The total of 98 strains of moulds were isolated from soils collected in arctic tundra (Spitzbergen). Among these strains Penicillium cyclopium 1, the most effective for production of catalase, was selected by the method of test-tube microculture. The time course of growth and catalase production by this strain showed the intracellular activity of this enzyme to be about 3-fold higher than its extracellular level Some properties of crude catalase preparation, isolated from postculture liquids by lyophilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 17 publications
(24 reference statements)
0
19
0
Order By: Relevance
“…However, ecophysiological characterizations of these taxa in terms of ther− mal characteristics have rarely been attempted. Taxa that have previously been de− scribed as psychrophilic or psychrotolerant include Mortierella alpina and Mucor hiemalis (Bergero et al 1999;Tosi et al 2002;Gawas−Sakhalkar andSingh 2011), P. lagerbergii (Bergero et al 1999), Geomyces pannorum (Mercantini 1989;Krishnan et al 2011), and Neonectria ramulariae (Fiedurek et al 2003;Chaverri et al 2011). However, the classification of some taxa based on the current study differed from previous reports, including that of Mortierella elongata (cf.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…However, ecophysiological characterizations of these taxa in terms of ther− mal characteristics have rarely been attempted. Taxa that have previously been de− scribed as psychrophilic or psychrotolerant include Mortierella alpina and Mucor hiemalis (Bergero et al 1999;Tosi et al 2002;Gawas−Sakhalkar andSingh 2011), P. lagerbergii (Bergero et al 1999), Geomyces pannorum (Mercantini 1989;Krishnan et al 2011), and Neonectria ramulariae (Fiedurek et al 2003;Chaverri et al 2011). However, the classification of some taxa based on the current study differed from previous reports, including that of Mortierella elongata (cf.…”
Section: Discussionmentioning
confidence: 51%
“…Both groups have been reported in other studies in the Arctic and Antarctic regions (Bergero et al 1999;Krishnan et al 2011;. The few identified species recorded previously in the Arctic region include Neonectria ramulariae in tundra (Fiedurek et al 2003) et al 2011) reported that filamentous fungi includ− ing the genera Mortierella, Geomyces, Phialocephala, Penicillium, and Mucor were the most frequently isolated taxa. Members of Mortierella, including M. alpina, M. clonocystis, and M. elongata were present in the current study.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The time of biotransformation of limonene to perillyl alcohol by the Pseudomonas putida was reported to be 5 d (Chatterjee & Bhattacharyya 2001). Mycelial cultures of Mortierella minutissima 01 showed a maximum bioconversion at 15°C (Table 3), which was similar to that of its growth optimum (20°C) (Fiedurek et al 2003). Higher optimum temperatures were reported for bioconversion of limonene to oxygenated products by Pen.…”
Section: Resultsmentioning
confidence: 66%
“…Fungi used in this study were isolated from soils (Fiedurek et al 2003) in Spitsbergen (lat 77°33¢ N long 14°30¢ E). The composition of media (BM) used for biotransformation of limonene is presented in Table 2.…”
Section: Microorganisms and Mediamentioning
confidence: 99%